Study on the bending behavior of biodegradable metal cerebral vascular stents using finite element analysis. (17th July 2020) - Shi, Weiliang; Li, Hongxia; Zhu, Tingzhun; Jin, Yifei; Wang, Hairui; Yang, Jianbing; Zhao, Danyang
Graphical abstract: Abstract: Excellent bending behavior is evaluated as the primary factor during the design of biodegradable metal cerebral vascular stents (BMCVSs), which enables vascular stents to be successfully delivered to the targeted location and avoids unnecessary damage to blood vessels. Unfortunately, this bending behavior has been barely investigated which limits the design of BMCVSs with optimal structures. Herein, six BMCVSs were designed and their bending process were simulated using finite element analysis (FEA) . Then, the effects of the stent bridge connection type and structure on the bending behavior were systematically analyzed and an universal mathematical model was further established, in which the influence of the structure parameters of the stent bridge on the flexibility of stents was considered. After that, the bending mechanism of the high-stress zone of the bridge was investigated. Finally, the causes and effects of the self-contacting phenomenon as well as the inner-stent protrusion phenomenon in the bending state were analyzed theoretically, and corresponding solutions were proposed to optimize the design of stents. The numerical results show that the stents with the dislocation-line W-shaped unit have better flexibility than the other stents. The flexibility is positively correlated to the cube of the length of linear part and to the square of the curvature of curved part. The self-contacting phenomenon of the bridge during bending can constrain the formation of inner-stent protrusion, which can eliminate the negative effects of the implanted stents on the hemodynamics in blood vessels. This study is expected to provide practical guidance for the structural design of BMCVSs for clinical applications.